Psychosocial experiences of prostate cancer survivors after treatment: a systematic review of qualitative studies - Xiang, Junlian; Dai, Lifei; Tan, Lin; Lv, Dong; Chen, Yongbo; Tang, Liangyou; Zhang, Jiali; Yi, Xin; Liu, Xiaoli (Frontiers in Public Health, 2025)
BackgroundProstate cancer, the second most common male malignancy worldwide, treatment-related complications cause both physical dysfunction and psychosocial sequelae, significantly impairing quality of life. Now requires integrated biopsychosocial rehabilitation beyond disease-focused treatment, comprehensive assessment of psychosocial adaptation and illness perception is essential for developing evidence-based, patient-centered rehabilitation strategies to optimize post-therapy recovery.ObjectiveThis study aims to systematically review and synthesize qualitative evidence on post-treatment psychosocial experiences in prostate cancer patients, thoroughly analyze patients’ lived experiences and coping strategies, and provide an evidence-based foundation for establishing a tiered psychosocial support system and developing clinical intervention protocols.MethodsThis systematic review followed the Joanna Briggs Institute (JBI) methodology for qualitative meta-aggregation, with reporting structured according to the ENTREQ statement. Evidence was graded using the ConQual approach and critically appraised with the JBI Qualitative Assessment and Review Instrument (JBI-QARI). We systematically searched six major English databases for qualitative or mixed-methods studies investigating psychosocial experiences in post-treatment prostate cancer patients, with the literature search updated to February 28, 2024. Two reviewers independently performed study selection, followed by collaborative thematic synthesis to identify core themes.ResultsA total of 22 studies from 12 countries were included, with 65 findings extracted and categorized into 4 synthesized findings consisting of 8 distinct categories: (1) Psychological and emotional responses (fear and anxiety responses, depression and emotional distress); (2) Healthcare information and systemic barriers (disease-related information needs, barriers in healthcare systems); (3) Social support and interpersonal adaptation (support system needs, social role and relationship adaptation); (4) Internal adaptation and external actions (internal psychological adjustment, external coping behaviors).ConclusionProstate cancer survivors face multifaceted psychosocial challenges during post-treatment recovery, with psychological and social responses impacting rehabilitation outcomes. Inadequate social support systems and gaps in healthcare information emerge as major barriers to recovery. To address these issues, healthcare providers should enhance communication effectiveness, while policymakers need to strengthen social support networks, government and corporate sectors should implement targeted policies, and family members should provide empathetic understanding and active encouragement, collectively fostering comprehensive patient support.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, CRD42024537363.